2010
DOI: 10.1016/j.bmc.2010.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Novel tricyclic pyrazole BRAF inhibitors with imidazole or furan central scaffolds

Abstract: Graphical abstract1j IC50 (BRAF) = 0.24 μM; IC50 (pERK) = 0.58 μM; GI50 (SRB) = 0.87 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In contrast, vemurafenib [20] and dabrafenib [21] bind to the DFG-in active conformation of the ATP binding site. These active conformation inhibitors are highly BRAF-selective compared to other kinases [20].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, vemurafenib [20] and dabrafenib [21] bind to the DFG-in active conformation of the ATP binding site. These active conformation inhibitors are highly BRAF-selective compared to other kinases [20].…”
Section: Resultsmentioning
confidence: 99%
“…Further study indicated that both pyrazole tricyclic moiety and imidazole ring played a crucial role in exerting the bioactivity. The replacement of tricyclic pyrazole by tricyclic triazole or six‐membered ring decreased inhibitory potency, this might be attributed to the steric clash or unfavorable electrostatic interaction with BRAF binding pocket …”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 99%
“…However, this changed when Davies et al described mutations of B-Raf in 66% of melanomas and at a lower frequency in a wide range of human solid cancers. 20 Further research revealed that approximately 2% of human malignancies carry a mutation in B-Raf, 312 with highest frequencies observed in melanoma and carcinomas of the colon, thyroid gland, ovary, and biliary tract. 21,313,314 Currently, more than 100 different B-Raf mutations were described, with V600E (formerly labeled as V599E) being by far the predominant lesion (Catalogue of Somatic Mutations in Cancer: www.sanger.ac.uk/genetics/ CGP/cosmic).…”
Section: Raf Mutations In Cancermentioning
confidence: 99%